Revised Zonal Subdivision Of The Late Miocene Nannoplankton Biostratigraphy For Kutei Basin - Panuju Panuju (Testing Center for Oil and Gas LEMIGAS, 2009)
Lithological complexity and intense hydrocarbon exploration with the objective of Late Miocene sediments in Kutei Basin has provided the impetus for more refined Late Miocene nannoplankton zonation than the standard global schemes of Martini (1971). Investigation to the quantitative nannoplankton analysis results in Kutei Basin has been done, and there is evident that the deltaic sediments of this basin give an excellent nannoplankton assemblage dataset to refine the Late Miocene biostratigraphy. Biostratigraphically, Late Miocene ranges from the middle part of zone NN9 to the middle part of zone NN12 of Martini zonation (1971). Zone NN11 is the most crucial zone to be refined since this zone has long time interval (more than 2m.a.). In this paper, this zone can be subdivided into 7 subzones (NN11a-NN11g) based on relatively permanent occurrences of 6 biomarkers. They are from the base to the top, as follow: FO Discoaster quinqueramus, LO. Minilitha convalis, LO Discoaster bergenii, FO Amaurolithus primus, FO Reticulofenestra rotaria, LO, Discoaster berggrenii, LO. Reticulofenestra rotaria and LO Discoaster quinqueramus. In spite of zone NN9, NN10 and NN12 which have relatively short stratigraphic ranges, each zone can also be subdivided into 2 subzones. The base and the top of zone NN9 is indicated respectively by the FO and LO Discoaster hamatus. It can be subdivided by the FO Discoaster prepentaradiatus into subzone NN9a and NN9b. Zone NN10 is marked by the LO Discoaster hamatus at the base and FO Discoaster quinqueramus at the top. It can be subdivided into subzones NN10a and NN10b by the LO Discoaster bollii. Zone NN12 is characterized by the LO Discoaster quinqueramus at the base and the FO Ceratolithus rugosus at the top. This zone can be subdivided into subzone NN12a and NN12b by the LO Helicosphaera intermedia.